2001
DOI: 10.1246/cl.2001.808
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Sensing Behavior of Crystals of an Imidazole-Type Clathrate Host upon Contact with Gaseous Carboxylic Acids

Abstract: The crystals of the title fluorescent clathrand exhibit a drastic fluorescence enhancement behavior upon contact with carboxylic acid vapors. The magnitude of the fluorescence change is greatly dependent on the enclathrated carboxylic acid molecules and increase in the following order: formic acid < acetic acid < propionic acid. To elucidate the enclathrated guest effects on the fluorescence properties of the crystals, the X-ray crystal structures have been determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…A large red-shift of the absorption and fluorescence maxima and the solid-state fluorescence quenching by strong donor-acceptor type π-π interactions of fluorescent dyes are known. [4][5][6][7][8][9][10] In fact, the fluorescence emission intensities of 1a-1c are in the order of 1c>1b>1a in the crystalline state. In the crystal of 1b, a donor-acceptor type of π-stacking between a pair of quinol enantiomers is observed, however, the rang of the π-stacking is less than that of 1a.…”
Section: Relation Between the Solid-state Fluorescence Properties Andmentioning
confidence: 99%
See 1 more Smart Citation
“…A large red-shift of the absorption and fluorescence maxima and the solid-state fluorescence quenching by strong donor-acceptor type π-π interactions of fluorescent dyes are known. [4][5][6][7][8][9][10] In fact, the fluorescence emission intensities of 1a-1c are in the order of 1c>1b>1a in the crystalline state. In the crystal of 1b, a donor-acceptor type of π-stacking between a pair of quinol enantiomers is observed, however, the rang of the π-stacking is less than that of 1a.…”
Section: Relation Between the Solid-state Fluorescence Properties Andmentioning
confidence: 99%
“…[3] We have recently developed novel benzofurano [3,2-b]naphthoquinol-type [4] , imidazo [5,4-a]anthraquinol-type [5] and phenanthro [9,10-d]imidazole-type [6] fluorescent hosts whose crystals exhibit a dramatic fluorescence enhancement upon inclusion of various gaseous amines, organic solvents and carboxylic acids, respectively. From the relation between the solidstate fluorescence properties and the crystal structures, it was confirmed that the destruction of π-π interactions between the fluorophores by guest enclathratation is the main reason for the guest-dependent fluorescence enhancement behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Several types of fluorescent hosts exhibit fluorescence enhancement behaviour with a blueshift in the fluorescence wavelength maximum upon inclusion of various organic solvent molecules. [5][6][7][8][9][10][11] From comparison of the X-ray crystal structures of the guest-free and several clathrate compounds, it was concluded that the changes in molecular arrangement by the formation of CH-π interactions and the destructions of π-π interactions and the intermolecular hydrogen bonds binding fluorophores by the enclathrated guest molecules are the main reason for the guest-dependent fluorescence enhancement and the blueshift in the fluorescence maximum of the crystals. In contrast, we reported that a new phenanthro [9,10-d]imidazole-type fluorescent host, [12] 2-[4-(diethylamino)phenyl]-1H-phenanthro [9,10-d]imidazole (1; Scheme 1), whose crys-cent intensity changes.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous works, we reported novel benzofurano [3,2-b]naphthoquinol-type, [5] imidazo [5,4-a]anthraquinol-type, [8] 5-hydroxy-5-substituent-benzo [b]naphtho[1,2-d]-furan-6-one-type [9] and phenanthro [9,10-d]imidazoletype [10] fluorescent hosts, whose crystals exhibit a dramatic fluorescence enhancement upon inclusion of various amines, organic solvents and carboxylic acids. In particular, imidazo [5,4-a]anthraquinol-type fluorophores, in which two tautomeric forms (A and B) are possible for the imidazole ring, can include various kinds of organic solvent molecules in the crystalline state by changing the tautomeric form of the imidazole ring.…”
Section: Introductionmentioning
confidence: 99%